PENDEFINISIAN STASIUN AKTIF GMU1 TAHUN 2012 DENGAN TITIK IKAT GPS REGIONAL DAN GLOBAL - , SRI REZKI ARTINI; , Ir. Nurrohmat Widjajanti, M.T, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
GNSS CORS station can receive signals from GNSS satellites and operates continuously for 24 hours. GMU1 is one station GNSS CORS in Indonesia which has been operating since 2009 in the Department of Geodesy, Faculty of Engineering, UGM. As a station that has a spatial position, the station always change with the movement of the earth's crust. Therefore, the position of the station needs to be defined continuously. In this research, defining the coordinates of the station GMU1 studied the effect of regional and global reference points in the determination of the high accuracy coordinates. This study used GNSS observation data for seven days, on July 14, 2012 to July 20, 2012 (doy 196 to doy 202) with a sampling rate of 30 seconds. This research processed seven projects using a variation of regional and global reference points with GAMIT/ GLOBK software. The analysis used significance of the difference coordinate t-test betwen two projects. The results showed that the use of global reference point resulted higher level accuracy of coordinate compared to the other projects. The result of global project is X(-2200206,97517 m ± 1,41 mm), Y(5924895,45335 ± 2,79 mm) , and Z (-855932,54726 m ± 0,87 mm). The results of t-test indicated that there was no statistically significant difference between the coordinates of global project and the other projects.